'It's complicated': Staff nurse perceptions of their influence on nursing students' learning. A qualitative descriptive study. (April 2018) - Hanson, Sarah E.; MacLeod, Martha L.; Schiller, Catharine J.
Abstract: Background: During both teacher-led clinical practica and precepted practica, students interact with, and learn from, staff nurses who work on the clinical units. It is understood that learning in clinical practice is enhanced by positive interactions between staff nurses and nursing students. While much is known about preceptors' experiences of working with nursing students, there is little evidence to date about staff nurses' perspectives of their interactions with students in teacher-led practica. Purpose: To understand teacher-led clinical practica from the perspective of staff nurses. Method: A qualitative descriptive approach answers the question: How do staff nurses perceive their contributions to nursing students' learning during teacher-led practica? Nine staff Registered Nurses (RNs) working within a regional acute care hospital in western Canada were interviewed using semi-structured interviews. Interview transcripts were analyzed using cross case analysis to discover themes and findings were checked by several experienced RNs. Results: Analysis showed that nurses' interactions with nursing students are complicated. Nurses want to "train up" their future colleagues but feel a heavy burden of responsibility for students on the wards. This sense of burden for the staff nurses is influenced by several factors: the practice environment, the clinical instructor, the students themselves, and the nurses' understanding of their own contributions to student learning. Conclusions: Staff nurses remain willing to support student learning despite multiple factors that contribute to a sense of burden during teacher-led practica. Workplace environment, nursing program, and personal supports are needed to support their continuing engagement in student learning. Nurses need to know how important they are as role models, and the impact their casual interactions have on student nurses' socialization into the profession.